Canadian nurse practitioner's quest for identity: A philosophical perspective - Marie-Elaine Delvin; Suzanne Braithwaite; Pilar Camargo Plazas (Elsevier, 2018)
The role of nurse practitioners in primary healthcare has been validated over the years and is now being considered as a key solution in various primary healthcare settings to the provision of comprehensive care. The context in which the role has been established positions nurse practitioners' practice within medical and nursing paradigms. As the healthcare system evolves, nurse practitioners must define their identity to advocate for roles that reflect their professional values. A historical overview highlighting the context in which the NP role expanded will guide a philosophical discussion regarding role identity. After exposing tensions between the nursing and medicine disciplines, Abbots' theory of profession will be utilized to understand the foundations leading to initial research on nurse practitioner integration within the healthcare system. Feminist philosopher bell hooks' discourse on marginality will serve as a platform to reflect on the nurse practitioner identity within the current social context. Foucault's notions of governmentality, parrhesia and care of the self will then guide reflections regarding ways for nurse practitioners to locate themselves as a profession. Keywords: Feminist, Foucault, Nurse practitioner, Role, Social justice